Treatment approaches for multiple Myeloma vertebral column lesions – Results from an international survey distributed to the AO spine knowledge forum tumor - Vanessa Hubertus; Emily J. von Bronewski; Lucius S. Fekonja; Anton M. Früh; Christian J. Entenmann; Hannah Miller; Charlotte Buhre; Michael G. Fehlings; Ilya Laufer; Peter Vajkoczy; Julia S. Onken (Brain and Spine)
Introduction: Vertebral fractures and epidural compression are common complications in Multiple Myeloma (MM). Although non-surgical management is generally preferred, internationally accepted management guidelines are lacking. This study aimed to assess current international treatment approaches and clinical conditions guiding decision-making in MM vertebral lesions. Research question: Assessing international treatment standards for MM vertebral column lesions. Material and methods: A survey was distributed to members of the AO Spine Knowledge Forum Tumor, an expert forum specialized on the treatment of oncologic spine disease. The survey consisted of 25 questions, of which 15 assessed the participant's background, clinical expertise, and experienced treatment standards regarding MM vertebral lesions, followed by ten fictional case examples with seven possible treatment scenarios each. Results: 51 international experts completed the survey, 51 % being of orthopedic, and 44 % of neurosurgical background, while 5 % were radio-oncologists. 84 % of the participants stated they “see vertebral lesions in MM in general as a non-surgical disease”. As strongest indicators to perform surgery, neurological deficits (74 %), and potentially unstable lesions (20 %) were chosen. Clinical and radiological follow-up is performed by 83 %, however only in 46 % at defined intervals. 89 % would choose “less invasive” surgical strategies in MM than in similar lesions related to metastatic spine disease. Discussion and conclusion: The participating experts agreed towards a more restrained and less invasive management of MM patients, however the applicability of surgical scores, standards for follow-up, and indications as well as surgical strategies for MM vertebral lesions varied widely, illustrating the need for international guidelines standardizing treatment.